2006
DOI: 10.1097/01.wnr.0000192738.31029.0a
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic changes in the exploratory and habituation profiles of heterozygous neuregulin-1 knockout mice

Abstract: The neuregulin-1 gene is widely expressed in the central nervous system and is associated with increased risk for schizophrenia. Using an ethologically based approach, the phenotype of neuregulin-1 heterozygous knockout mice was examined by revealing the individual elements of behaviour in the murine repertoire over the prolonged course of interaction with the environment. During initial exploration, neuregulin-1 mutants displayed a phenotype characterized by increases in locomotion and rearing free, with sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 25 publications
9
71
1
Order By: Relevance
“…22 Finally, mouse models with disruptions in NRG1-ERBB4 signaling appear to capture some of the behavioral phenotypes associated with schizophrenia, and in certain cases these altered behaviors can be ameliorated by antipsychotics. 1,[23][24][25] Altogether, the data support a role for abnormal NRG1-ERB signaling in schizophrenia. Dissecting the pathways of NRG1-ERB signaling in the central nervous system may therefore contribute to the elucidation of pathways of schizophrenia susceptibility and may also reveal targets for interventions.…”
Section: Introductionsupporting
confidence: 55%
“…22 Finally, mouse models with disruptions in NRG1-ERBB4 signaling appear to capture some of the behavioral phenotypes associated with schizophrenia, and in certain cases these altered behaviors can be ameliorated by antipsychotics. 1,[23][24][25] Altogether, the data support a role for abnormal NRG1-ERB signaling in schizophrenia. Dissecting the pathways of NRG1-ERB signaling in the central nervous system may therefore contribute to the elucidation of pathways of schizophrenia susceptibility and may also reveal targets for interventions.…”
Section: Introductionsupporting
confidence: 55%
“…The value of an ethologically based approach to behavioural characterisation of mutant mice is increasingly recognised. It can identify novel phenotypic effects and resolve apparent inconsistencies in phenotype [4,7,22,23]. We have developed and applied such an approach to mice with knockout of each of the five DA receptor subtypes and components mediating DA receptor signal transduction [28].…”
mentioning
confidence: 99%
“…Having applied this approach to NRG1 mutants [22,23], in the present study we examine in the same manner the functional role of the COMT gene. This allows us to address two critical questions.…”
mentioning
confidence: 99%
“…As described previously (Nally et al, 2004;O'Sullivan et al, 2004O'Sullivan et al, , 2006O'Tuathaigh et al, 2006), for specification of the agonist-induced ethogram, the total 'counts' for each individual behavior were determined as the number of 5 s observation windows in which a given behavior was evident, summed over the 3 × 15 min [0 -15, 20 -35, 40 -55] cycle periods; data were expressed as means ± SEM. Stereotypy scores were averaged over the 60 min period and expressed similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were then allowed to habituate for a period of 3 h to reduce initially high levels of activity in order to optimise detection of agonist-induced stimulatory effects. Immediately following challenge with SKF 83822 (0.016 -2.0 mg/kg s.c.) or vehicle, assessments were carried out using a rapid time-sampling behavioral checklist technique and stereotypy rating scale, as previously described (Nally et al, 2004;c, 2006;O'Tuathaigh et al, 2006). For this study, the following components of the ethogram are reported: sniffing (flaring of nostrils with movement of vibrissae); locomotion (coordinated movement of all four limbs producing a change in location); rearing to wall (front paws reaching upwards onto or towards a cage wall while standing on hind limbs); total grooming (grooming of any form); intense grooming (characteristic, programmed syntax of sequential grooming of the snout and then the face with the forepaws, followed by grooming of the hind flank/anogenital region with the snout); seizures, characterised as any of the following phases occurring within the 60 min observation period: phase 1 = sustained immobility/rigidity; phase 2 = rearing with forepaw myoclonus; phase 3 = generalized clonus; phase 4 = tonic-clonic seizure or rapid jumping and wild running (Ferraro et al, 1999;McKhann et al, 2003;O'Sullivan et al, 2006); stillness (motionless: awake with no behavior evident, or asleep).…”
Section: Behavioral Assessmentmentioning
confidence: 99%